Artillery Strike Effectiveness in the Virtual Battlefield - Hou Chenyu; Chen Jiawei; Hou Yuguan; Shen Yiying (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Artillery plays an irreplaceable role in modern warfare. But due to its huge destructive power, artillery experiment is dangerous and costly. Computer simulation technology uses mathematical models to replace the missile systems and thus avoid accidents and save funds. Based on the trajectory equation model, this paper presents a computer simulation of the projectile distribution. Then, by the simulation results, this paper analyzes each factor’s influence on the fall point’s distribution, as well as the distribution type and distribution parameters. The damage probability and the average amount of ammunition are calculated to assess the strike effectiveness. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.876